2023
DOI: 10.1177/14648849231194485
|View full text |Cite
|
Sign up to set email alerts
|

Shortcuts to trust: Relying on cues to judge online news from unfamiliar sources on digital platforms

Amy A Ross Arguedas,
Sumitra Badrinathan,
Camila Mont’Alverne
et al.

Abstract: Scholarship has increasingly sought solutions for reversing broad declines in levels of trust in news in many countries. Some have advocated for news organizations to adopt strategies around transparency or audience engagement, but there is limited evidence about whether such strategies are effective, especially in the context of news consumption on digital platforms where audiences may be particularly likely to encounter news from sources previously unknown to them. In this paper, we use a bottom-up approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In France, as in many other countries, most people—even heavy social media users—are particularly distrustful of the information that circulates on social media [ 52 ]. Also, the circulation of information on social media tends to be segmented; meaning that different users will come across different types of information [ 72 ]. In the case of vaccination in France, a recent study of the spread of vaccine critical contents on Twitter during the COVID-19 epidemic found that vaccine critical activists had a limited ability to reach a wide audience, despite their intense activity [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In France, as in many other countries, most people—even heavy social media users—are particularly distrustful of the information that circulates on social media [ 52 ]. Also, the circulation of information on social media tends to be segmented; meaning that different users will come across different types of information [ 72 ]. In the case of vaccination in France, a recent study of the spread of vaccine critical contents on Twitter during the COVID-19 epidemic found that vaccine critical activists had a limited ability to reach a wide audience, despite their intense activity [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gradual decrease in trust in media worldwide over recent decades (Newman et al 2023) has fueled a wide range of studies on this phenomenon (Fisher 2016;Daniller et al 2017;Arguedas et al 2023). Recent attempts to conceptualize trust in media have highlighted several challenges in this strand of research (Strömbäck et al 2020;Prochazka and Schweiger 2019;Majerczak and Strzelecki 2022).…”
Section: Trust In News In and Beyond The Western Worldmentioning
confidence: 99%
“…In the rich media environment, people tend to be exposed to an almost endless variety of information sources with a very little or no knowledge about their background and reputation. Arguedas et al (2023) have analyzed construction of trust in unfamiliar sources exploring different kinds of cues which help people "more quickly and efficiently judge the trustworthiness of the news" (p. 24), "especially when it came to news from sources they did not habitually use or have significant knowledge about" (p. 10), and concluded that some specific cues were more or less easily noticeable depending on the media context. According to their findings, the variation across countries was less salient than across particular platforms-news websites, social media (Facebook), messaging apps (WhatsApp), and search engines (Google), the usage of which has resulted "in different kinds and combinations of heuristics" (p. 26).…”
Section: Trust In News In and Beyond The Western Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows the Patrick Moore subnetwork distinctly removed from the main component of the global network. The polarised structure (Himelboim et al, 2017), and the differences in the information shared and attitudes of the global network compared with the Patrick Moore subnetwork, are analytical indicators of potential ideological and affective polarisation (Ross Arguedas et al, 2022). However, further analysis is needed of actors, content, information-sharing patterns, and in-group and out-group sentiment at an inter- and intra-cluster level (Dehghan et al, 2020).…”
Section: Dominant Actors and Information Flowsmentioning
confidence: 99%